2019
DOI: 10.1021/acsami.9b15817
|View full text |Cite
|
Sign up to set email alerts
|

High-Strength, Self-Adhesive, and Strain-Sensitive Chitosan/Poly(acrylic acid) Double-Network Nanocomposite Hydrogels Fabricated by Salt-Soaking Strategy for Flexible Sensors

Abstract: As a promising functional material, hydrogels have attracted extensive attention, especially in flexible wearable sensor fields, but it remains a great challenge to facilely integrate excellent mechanical properties, self-adhesion, and strain sensitivity into a single hydrogel. In this work, we present high in strength, stretchable, conformable, and self-adhesive chitosan/poly­(acrylic acid) double-network nanocomposite hydrogels for application in epidermal strain sensor via in situ polymerization of acrylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
182
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(185 citation statements)
references
References 58 publications
2
182
1
Order By: Relevance
“…These results demonstrate that agar/PAAm-CNFs hydrogel sensor showed remarkable stability, which is comparable to previously reported hydrogel-based strain sensors. [6,37] Under ambient conditions, the water in hydrogels may volatilize in a long term leading to the upward drift of ΔR/R 0 , although silicone oil is coated on the hydrogel surface. In addition, as shown in Figure S11, the hydrogel strain sensors with other conductive nanofillers, CNTs and GNPs, also exhibited good stability under cyclic stretching.…”
Section: Piezoresistivity Of the Conductive Hydrogel Strain Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrate that agar/PAAm-CNFs hydrogel sensor showed remarkable stability, which is comparable to previously reported hydrogel-based strain sensors. [6,37] Under ambient conditions, the water in hydrogels may volatilize in a long term leading to the upward drift of ΔR/R 0 , although silicone oil is coated on the hydrogel surface. In addition, as shown in Figure S11, the hydrogel strain sensors with other conductive nanofillers, CNTs and GNPs, also exhibited good stability under cyclic stretching.…”
Section: Piezoresistivity Of the Conductive Hydrogel Strain Sensorsmentioning
confidence: 99%
“…In this study, the investigated CNF concentration (0.25 1 wt%) is assumed in the range of tunnelling junction or complete contact, which can be evidenced by the decrease of electrical resistance, for example, from 40 kΩ for the blank hydrogel to 30 kΩ for the hydrogel with 0.75 wt% CNFs. PAA-PEDOT:sulfonated lignin 7.0 3.01 100 [33] CS/PAA-TA@CNC 3.0 1.66 300 [37] PAAm-oxCNTs 3.39 1.54 700 [46] PVA/PVP-CNCs-Fe 3+ 0.478 0.61 200 [70] κ-Carrageenan/PAAm 0.23-0.63 0.83 b 1,000 [63] PAA/PANI 0.6-1.05 1.02 b 1,130 [36] PNIPAAm/PANI 3.9 2.20 120 [71] PVA/PEDOT:PSS 4.4 2.43 100 [34] Gelatin-silver nanowires 4.5 2.10 200 [41] Ethylenediamine-PT/rGO 7.98 3.89 52.8 [72] Abbreviations: CNFs, carbon nanofibers; CNT, carbon nanotube; GF, gauge factor; GO, graphene oxide; PAAm, polyacrylamide; PANI, polyaniline; PEDOT, poly(3,4-ethylenedioxythiophene); SEM, scanning electron microscope.…”
Section: Microstructure Of Sensors and Strain-sensing Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] The researches on PAA and other macromolecules forming double network adhesive hydrogels with reversible and strong adhesion (25 KPa) to multiple polar substrates and electrical conductivity also continuously emerge. [33][34][35] Except for that, it was reported that NHS achieves strong chemical adhesion, it has become a research hotspot in recent years, and then it achieves efficient peeling of NHS adhesion through disulfide bonds. [36] In fact, NHS functional groups can undergo cross-linking reactions with amino groups in proteins on the tissue surface to form chemical bonds.…”
Section: Introductionmentioning
confidence: 99%
“…These strategies have been developed mainly for the repair and regeneration of NP of the degenerated IVD [10][11][12]. Over the past few years, great efforts have been devoted to the design of innovative biomaterials for the repair/regeneration of nucleus pulposus in laboratory settings, such as bovine biomimetic NP scaffold [13], multi-polymers [14], injectable hydrogels [15][16][17][18], and cellular and cell-laden hydrogels [19,20]. However, scaffold-based NP repair without giving much regard to NP could not recover the complex microenvironment structure for cell attachment, proliferation, and migration, which might make the disc degenerative change continuously exacerbate.…”
Section: Introductionmentioning
confidence: 99%